GAYA BAHASA PENGULANGAN KISAH NABI MUSA AS. DALAM AL-QURâAN: SUATU KAJIAN STILISTIKA - Mursalim, Mursalim (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Stories related to Moses are among the most frequently cited stories found in the Qurâan. This is, in part, due to the similarity of social context of Daâwa between Muhammad and Moses. Thus, the aim of this research is to understand how the Qurâan repeat those stories by stylistically scrutinizing each verses in the Qurâan related to Moses. This paper applies a combination of library research method using descriptive-analytical technique and mauduâI technique of Qurâanic interpretation. Findings of this research show that there are, at least, three linguistics styles in which the Qurâan repeat verses related to Moses; one related to using different linguistic styles, one related to using different actors, and one related to using different theme and chronological order. However, all of them revolves around the topic of advices for Muhammad in particular and humankind in general, in dealing with his social reality of Daâwa context.